1984
DOI: 10.1111/j.1471-4159.1984.tb06079.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Rat Brain Metabolism Using Proton Nuclear Magnetic Resonance: Spectral Assignments and Monitoring of Prolidase, Acetylcholinesterase, and Glutaminase

Abstract: The first application of inversion-recovery spin-echo proton nuclear magnetic resonance spectroscopy to the monitoring of reactions in rat brain preparations is presented. The initial report of the assignment of proton spin-echo nuclear magnetic resonance spectra from rabbit brain homogenates (C. R. Middlehurst et al., J. Neurochem. 42, 878-879, 1984) was used to assist in the assignment of spectra acquired from rat brain homogenates that were obtained from animals killed by cervical fracture or focussed micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Its presence has been reported in several cell culture and extract studies, though its abundance was questioned as a possible artifact of the sample preparation. 11 Nevertheless, it has been observed in high-resolution NMR studies of normal rat brain, 30 human resected tissues, 31 and cell cultures, 32 and to be present at a high concentration in neonatal rat cerebellum with a progressive decrease with age. 33 Concentrations in human brain are approximately 0.4-0.8 mmol/kg ww , 31 with increased levels observed in brain tumors, 34 ischemia, 35 and in vivo in brain abscesses.…”
Section: Acetate (Ace)mentioning
confidence: 99%
“…Its presence has been reported in several cell culture and extract studies, though its abundance was questioned as a possible artifact of the sample preparation. 11 Nevertheless, it has been observed in high-resolution NMR studies of normal rat brain, 30 human resected tissues, 31 and cell cultures, 32 and to be present at a high concentration in neonatal rat cerebellum with a progressive decrease with age. 33 Concentrations in human brain are approximately 0.4-0.8 mmol/kg ww , 31 with increased levels observed in brain tumors, 34 ischemia, 35 and in vivo in brain abscesses.…”
Section: Acetate (Ace)mentioning
confidence: 99%
“…Later work suggested that other brain constituents having N-acetyl moieties (e.g., N-acetylaspartylglutamate), also contribute to signal intensity in this region of the spectrum (5,6). Published evidence also shows that glutamate, glutamine, and various macromolecular constituents contribute to this spectral region (4,(7)(8)(9)(10)(11)(12), although it is unlikely that these latter signals are present in long echo time spectra, of the sort we present here, due to T, and J-modulation losses (12). Despite the controversy, most investigators accept the notion that NAA is a major contributor to the 2.02 ppm signal.…”
Section: Introductionmentioning
confidence: 51%
“…'H-MRSI is not without disadvantages. High resolution 2-dimensional phase encoding is time consuming and performing studies with TR values that are [5][6][7][8][9][10] times the longest in vivo T, values are usually not practical. Consequently, 'H-MRSI data are often moderately TI-weighted.…”
Section: Discussionmentioning
confidence: 99%
“…Glutaminase activity can be readily monitored by using 400MHz 1H-n.m.r. since the glutamine and glutamate Hy protons have significantly different chemical shifts (Middlehurst et al, 1984). Incubation of rabbit or human erythrocyte lysates or whole cell suspensions (haematocrit 0.70-0.80) with glutamine (5 mmol/l) led to no detectable production of glutamate (i.e.…”
Section: Assay Of Glutaminase Activitymentioning
confidence: 99%
“…Proton spin-echo n.m.r. spectroscopy was used in these studies because of its now well-documented ability to monitor the kinetics of peptide transport and hydrolysis in situ (King et al, 1983;Middlehurst et al, 1984).…”
mentioning
confidence: 99%